Sport clubs in Brazil: facilities, equipment and content in - Jessica Cristiani; João Carlos Bressan; Benjamín Longarela Pérez; Larissa Rafaela Galatti; Riller Silva Reverdito (Federación Extremeña de Balonmano; University of Extremadura, 2017)
Sport is an important phenomenon on XXI Century, and sport clubs are a relevant environment for youth sport. Aim: analyze facilities, equipment and contents in social-clubs in Cáceres City (Mato Grosso State, Brazil). Method: for collecting data we applied participatory observation, with researcher journal and semi-structured questioners. Results and Discussion: we found the following facilities and equipment: swimming pools (n=8), sport courts (n=4), soccer fields (n=10), fitness rooms (n=1), tennis courts (n=2), sand fields (n=4). The most common activities are related with swimming and soccer, in a sport participation perspective. Only one club had a sport development program, just in soccer. One club has coaches with bachelor degree in Physical Education. Conclusions: clubs offer a good sport structure for systematized sport practice, however, facilities and equipment are underused, and with insufficient qualified coaches.